Analysis of C1, C2 screw fixation for atlantoaxial instability in patients of different age groups - Alexandr V. Gubin; Aleksandr V. Burtsev; Sergey O. Ryabykh; Vladimir S. Klimov; Aleksey V. Evsyukov; Denis S. Ivliev (Хирургия позвоночника, 2018)
Objective. To analyze feasibility and safety of C1, C2 fixation for craniocervical stabilization in patients of different age groups. Material and Methods. Study design is a retrospective multicenter cohort analysis. Level of evidence – II. The study was based on the diagnosis and treatment data of 43 patients aged 5–74 years who underwent C1, C2 screw fixation. Results. In most cases, atlantoaxial instability was due to traumatic injuries. Screws were implanted in C1 in 81 cases, and in C2 in 80. Postoperative MSCT data were evaluated in 41 patients. The position of the screws in C1 was defined as ideal in 63,0 % of cases, in the remaining cases there were malpositions, with 6 screws having double malpositions. Out of 80 screws inserted in C2, 64 were implanted transpedicularly. In 59.5 % of cases, a good position was revealed; in other cases different malpositions were noted. In none of the cases neurovascular damage or clinical manifestation occurred. Conclusion. Analysis of screw fixation of C1, C2 showed that this technique is feasible in patients of different age groups. Duration of surgery and blood loss did not go beyond the conventional values. Postoperative malpositions are not accompanied by neurological disorders, which allows to consider this fixation quite safe.